LAPORAN KASUS POTENSI INTERAKSI OBAT DAN PENINGKATAN EFEK HIPOTENSI PADA PERAWATAN INTENSIVE PASIEN SKIZOFRENIA DENGAN HIPERTENSI - Julaeha Julaeha; Intan Nada Nugrahani (Jurnal Insan Farmasi Indonesia, 2021)
Schizophrenia is a serious and chronic mental disorder, that can reduce the quality of human life. In Indonesia, almost 70% of those treated in the psychiatry department were due to schizophrenia. Prevalence The incidence of schizophrenia in men is greater than in women, the incidence in men is 1.4% greater than women. In this case, a 58-year-old male patient came to the hospital, the initial diagnosis was unspecified schizophrenia and Hypertension. The patient was restless when he entered the hospital, beat his wife, broke household appliances, and threw stones at a neighbor's house. Patient's vital signs upon admission to hospital Blood pressure 160/95 mmHg, 37.7oC of temperature, pulse 99x/minute Breathing 17x/minute. The patient was treated with risperidone 1 mg, lorazepam 0.5 mg, candesartan 8 mg, and amlodipine 5 mg. From the results of monitoring drug therapy, potential drug interactions might be occurred i.e drug interaction between lorazepam and risperidone, both of which can increase sedation effect. The interaction between risperidone and trihexyphenidyl might be enhance the anticholinergic effect. In addition, antipsychotics could potentially enhance the hypotensive effect and SGPT serum elevated. Close monitoring of psychosis symptoms and blood pressure should be done to ensure the efficacy and safety of medications